2018
DOI: 10.1007/s00262-018-2248-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of everolimus and low-dose oral cyclophosphamide in patients with metastatic renal cell carcinoma

Abstract: mTOR inhibitors are frequently used in the treatment of metastatic renal cell cancer (mRCC). mTOR regulates cell growth, proliferation, angiogenesis, and survival, and additionally plays an important role in immune regulation. Since mTOR inhibitors were shown to benefit immunosuppressive regulatory T-cell (Treg) expansion, this might suppress antitumor immune responses. Metronomic cyclophosphamide (CTX) was shown to selectively deplete Tregs. This study was, therefore, designed to determine the optimal dosage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…One possibility is that the dosing regimen of cyclophosphamide used in this study was not optimal for Treg depletion. Since the completion of our study, emerging data showed that oral cyclophosphamide may be more effective for Treg depletion 35,36 . Given these limitations, future studies may be required to fully characterize the evolution of the immune TME over time and to optimize neoadjuvant immunotherapy in patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 96%
“…One possibility is that the dosing regimen of cyclophosphamide used in this study was not optimal for Treg depletion. Since the completion of our study, emerging data showed that oral cyclophosphamide may be more effective for Treg depletion 35,36 . Given these limitations, future studies may be required to fully characterize the evolution of the immune TME over time and to optimize neoadjuvant immunotherapy in patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 96%
“…The trial was initiated by the department of medical oncology of the Amsterdam UMC, location VUmc and conducted within the context of the Netherlands Working Group on Immunotherapy of Oncology (WIN-O) with participation of 13 hospitals and enrollment of patients from January 2012 until August 2015. Clinical findings were reported separately [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patients were treated in cohorts of five patients, with six different doses and schedules of CTX. Clinical results and results of changes in Treg frequencies in the various cohorts of this phase 1 trial were separately described [ 17 ]. Here, we report on the results of the extensive and comprehensive immune monitoring that was additionally performed in this phase 1 study, where patients were treated with either everolimus alone or the combination of everolimus and different CTX administration dosages and schedules.…”
Section: Introductionmentioning
confidence: 99%
“…Everolimus has also been tested in cervical cancer cell lines with a remarkable ability to inactivate efficiently the HPV16 E7 oncoprotein inhibiting cell proliferation (202). The capacity of everolimus-based combinations to inhibit cell proliferation from several cancer types has been reported for breast cancer (203,204), renal cell carcinoma (205,206), and thyroid cancer (207) in clinical trials.…”
Section: Mtorc1 As a Therapeutic Targetmentioning
confidence: 99%